\(2018\cdot2018-2017\cdot2019\)
\(=2018^2-\left(2018-1\right)\left(2018+1\right)\)
\(=2018^2-\left(2018^2-1\right)\)
\(=2018^2-2018^2+1\)
\(=1\)
\(2018.2018-2017.2019\)
\(=2018^2-\left(2018-1\right)\left(2018+1\right)\)
\(=2018^2-\left(2018^2-1\right)\)
\(=2018^2-2018^2+1\)
\(=1\)
nhớ k đấy
2018*2018-2017*2019
=2018*(2019-1)-2017*2019
=2018*2019-2018-2017*2019
=2019-2018=1
\(2018\times2018-2017\times2019\)
\(=2018^2-\left(2018-1\right)\times\left(2018+1\right)\)
\(=2018^2-\left(2018^2-1\right)\)
\(=2018^2-2018^2+1\)
\(=1\)
_Chúc bạn học tốt_
\(2018\times2018-2017\times2019\)
\(=2018^2-\left(2018-1\right)\left(2018+1\right)\)
\(=2018^2-2018\left(2018-1\right)+2018-1\)
\(=2018^2-2018^2-2018+2018-1\)
\(=\left(2018^2-2018^2\right)+\left(2018-2018\right)-1\)
\(=0+0-1\)
\(=0-1\)
\(=-1\)